Evaluation of treadmill cardiopulmonary exercise testing and field measurement results in women’s youth and adult national team water polo players - Mark Zamodics; Mate Babity; Attila Mihok; Csaba Bognar; Agnes Bucsko-Varga; Panka Kulcsar; Dora Boroncsok; Regina Benko; Alexandra Fabian; Balint Lakatos; Hajnalka Vago; Attila Kovacs; et al. (Heliyon)
The benefits of treadmill-based cardiopulmonary exercise testing (CPET) are well known. However, water polo trainings involve completely different movements in a distinct environment.Our objective was to analyze data from elite youth and adult water polo players, gathered through CPET and age- and sport-specific swimming tests. Resting and exercise heart rate, as well as lactate levels, were examined at specific time points during both assessments. Additionally, maximal aerobic capacity was evaluated during the CPET.Forty-six female water polo players were examined (age:18.5 ± 5.9 y, adults:19). No significant differences were found between CPET and swimming tests for resting heart rate (75[IQR:65–85] vs. 71[IQR:63–81] BPM, p = 0.33) and lactate levels (1.5[IQR:1.1–1.7] vs. 1.5[IQR:1.3–1.7] mM, p = 0.33). Maximal heart rates were higher during CPET than swimming (196.3 ± 9.7vs.191.0 ± 12.5 BPM, p < 0.001), while maximal lactate levels were lower (8.4 ± 2.4vs.9.6 ± 2.7 mM, p < 0.05).Lactate levels remained elevated after routine cool-down swimming ordered by the trainers, but decreased after suggested further training (6.6 ± 2.7vs.3.7 ± 1.6 mM, p < 0.001). Comparing the youth (<18y) and the adult (≥18y) players, no differences in relative maximal aerobic capacity (44.4 ± 4.8vs.44.9 ± 5.5 ml/kg/min, p = 0.72) and in peak lactate values (8.2 ± 2.7vs.8.7 ± 1.9 mM, p = 0.48) were observed in CPET examinations, while maximal heart rates were higher in the youth group (200.7 ± 7.2vs.190.1 ± 9.6 BPM, p < 0.001).Similarly, maximal lactate levels showed no differences (9.1 ± 2.6vs.10.4 ± 2.7 mM, p = 0.13), while maximal heart rates were higher in the youth group during swimming examinations (197.7 ± 10.0vs.181.4 ± 8.9 BPM, p < 0.001).The combined use of both exercise tests enables the assessment of maximal physiological parameters (heart rate, lactate, aerobic capacity) during different types and intensities of physical exercise and identifies differences across age groups, facilitating the design of a more personalized and effective training program.